A single-center analysis of genotype–phenotype characteristics of Chinese patients with autosomal dominant polycystic kidney disease by targeted exome sequencing - Yan, Ziyan; Wang, Yuchen; Deng, Wenfeng; Zhou, Yi; Hu, Yangcheng; Qi, Ka; Liu, Ding; Xia, Renfei; Liu, Rumin; Zeng, Wenli; Zhang, Wei; Xu, Jian; et al. (Frontiers in Genetics, 2022)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is mainly caused by PKD1 and PKD2 mutations. However, only a few studies have investigated the genotype and phenotype characteristics of Asian patients with ADPKD. This study aimed to investigate the relationship between the natural course of ADPKD genotype and phenotype. Methods: Genetic studies of PKD1/2 genes of Chinese patients with ADPKD in a single center were performed using targeted exome sequencing and next-generation sequencing on peripheral blood DNA. Results: Among the 140 patients analyzed, 80.00% (n=112) harbored PKD1 mutations, 11.43% (n=16) harbored PKD2 mutations, and 8.57% (n=12) harbored neither PKD1 nor PKD2 mutations. The average age at dialysis was 52.60±11.36, 60.67±5.64, and 52.11±14.63 years, respectively. The renal survival rate of ADPKD patients with PKD1 mutations (77/112) was significantly lower than that of those with PKD2 mutations (9/16), leading to an earlier onset of end-stage renal disease (ESRD). Renal prognosis was poor for those with nonsense mutations and they required earlier renal replacement therapy. Conclusions: The genotype and phenotype characteristics of ADPKD patients potentially vary across ethnic groups. Our findings supplement the genetic profiles of Chinese ADPKD patients, could serve as a guide for therapy monitoring and prognosis assessment of ADPKD, and may improve the clinical diagnosis.